PEMBUATAN KARYA FILM PENDEK “TERSESAT” MENGGUNAKAN TEKNIK PENYUTRADARAAN DENGAN GAYA REALIS - Risang Adji Lestariawan; Hans Hermang Mintana (AKADEMI KOMUNIKASI RADYA BINATAMA, 2023)
ABSTRACTThis report describes the application of the Realist style to the directing technique of the short film Tersesat. As a report review, definitions, theories, characteristics, and characters of the Realist style are also disclosed. Furthermore, it was explained that the director chose a Social Realist style combined with Laissez Faire leadership theory to build the dramatic and artistic aspects of the production of the short film Get Lost.The results of the report explain that the Social Realist style is considered appropriate in the directing technique of the short film Tersesat. This is because the main character of the story, who is a family of farmers, is part of the proletariat, in accordance with the characteristics of the main character in the Social Realist style. In addition, the characteristics of the Social Realist style that uses natural acting are also appropriate to be applied to build the illusion of reality in the production of the short film Tersesat.Kata kunci : Film fiksi drama, Tersesat, Sutradara, Realisme